AUDIT SISTEM INFORMASI PENGAWASAN DAN PEMANTAUAN PERMINTAAN LAYANAN DAN INSIDEN MENGGUNAKAN COBIT 5 PADA PT TELKOM REGIONAL WHOLESALE SERVICE 3 JAWA BARAT - Tri - Ramdhany (FKOM UNIKU, 2020)
PT Telkom has an information system that acts as a surveillance and monitoring management by having an inventory function (production equipment data requirements), fulfillment of customer needs and assurance (guaranteed service provided). So that it can facilitate the improvement of service to customers to manage new installations, monitor and follow up if there is a disruption every time. Monitoring information system and monitoring of service requests incidents as well as supporting the implementation of business processes are used to achieve company goals. Therefore, an audit is carried out to determine the suitability of the monitoring information system and monitoring of service requests incidents with the company's objectives, using the COBIT 5 framework in the DSS (Deliver, Service and Support) domain. Based on the results of mapping using COBIT 5 obtained from the company's strategy mapped into enterprise goals and IT-related goals so that the process to be assessed is DSS02 (Manage Service Request and Incident). Results obtained for the DSS02 process at levels 1 and 2 have been achieved because the achievement results exceed 85% which means that there is evidence of the process being assessed and full achievement, so the final achievement for the DSS02 process is at level 3 namely the Established Process that the managed process has been implemented using a process definition which is able to achieve the results of the process. From the results, it can be concluded that the current conditions and expected there is a gap of 0.42 to reach level 4, so recommendations are made in order to achieve its targets and implement one of the recommendations that have been obtained.Keywords: Audit, customer service, COBIT 5